2020
DOI: 10.2327/jjvas.51.8
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Melanoma on the Nasal Planum Treated with Nasal Planectomy in a Cat

Abstract: Non-ocular melanocytic tumor (NOMT) is rare in cats. NOMTs with high proliferative activity on the nose have been suggested to have a poor prognosis, but there is little information on treatment. We performed a nasal planectomy in a cat with a rapidly growing NOMT on the nasal planum. Histologically, the resected tumor was composed of nongranular epithelioid and spindle cells with moderate nuclear atypia and frequent mitotic figures, and it was diagnosed as a malignant melanoma. The tumor cells were near the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Os animais acometidos com o leiomioma e hiperplasia endometrial cística constantemente apresentam sinais clínicos de sangramento vulvar, além de outros sinais como aumento do abdomen, desconforto abdominal, desordem mamária, letargia e anorexia. Contudo, alguns animais ainda podem se apresentar de forma assintomática e não serem identificados (SAITO et al, 2002;RAIMUNDO, 2022;KOJIMOTO et al, 2021;QUESENBERRY et al, 2021;MÄKITAIPALE et al, 2022) (2002), os dados mostraram que 28,79% (14/47) dos animais estavam acometidos com HEC, e em outro estudo feito por Walter et al (2010) 40,68% (24/59) dos animais possuíam a mesma enfermidade. Em humanos e cães, os leiomiomas são as neoplasias diagnosticadas com maior frequência, porém em coelhos a ocorrência é menos frequente (RICHTER et al, 2006;SOUZA et al, 2008;CHEN;NOVO, 2018;LIMA;ANDREUSSI, 2019;SILVESTRE, 2019).…”
Section: Resultados E Discussõesunclassified
“…Os animais acometidos com o leiomioma e hiperplasia endometrial cística constantemente apresentam sinais clínicos de sangramento vulvar, além de outros sinais como aumento do abdomen, desconforto abdominal, desordem mamária, letargia e anorexia. Contudo, alguns animais ainda podem se apresentar de forma assintomática e não serem identificados (SAITO et al, 2002;RAIMUNDO, 2022;KOJIMOTO et al, 2021;QUESENBERRY et al, 2021;MÄKITAIPALE et al, 2022) (2002), os dados mostraram que 28,79% (14/47) dos animais estavam acometidos com HEC, e em outro estudo feito por Walter et al (2010) 40,68% (24/59) dos animais possuíam a mesma enfermidade. Em humanos e cães, os leiomiomas são as neoplasias diagnosticadas com maior frequência, porém em coelhos a ocorrência é menos frequente (RICHTER et al, 2006;SOUZA et al, 2008;CHEN;NOVO, 2018;LIMA;ANDREUSSI, 2019;SILVESTRE, 2019).…”
Section: Resultados E Discussõesunclassified
“…One previous case study of a nasal melanoma in a cat showed that nasal planectomy was a successful treatment with no recurrence at 5 years. 11 In this case, the owners found surgery an unacceptable option owing to its radical and invasive nature, as well as concerns regarding the cosmetic outcome, and so this was not pursued.…”
Section: Discussionmentioning
confidence: 99%